Formed sheet metal part with improved welding properties
By setting an aluminum-based anti-corrosion coating on the steel substrate, the welding properties are optimized, and the welding instability caused by natural oxide layers is solved, thereby achieving higher welding reliability and wider welding current selection.
Patent Information
- Application Number
- CN202380048788.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-21
- Filing Date
- 2023-06-20
- Publication Date
- 2025-02-07
AI Technical Summary
The existing aluminum-based coating forms a natural oxide layer at high temperatures, resulting in an increase in volume resistance during welding, affecting connection reliability, and limited welding current selection and low process reliability.
By providing an aluminum-based anti-corrosion coating on the steel substrate, the coating consists of an Al base layer and an alloy layer. The alloy layer is located above the steel substrate and the aluminum base layer is located above the alloy layer. The composition and production parameters of the alloy layer and the aluminum base layer match each other. To optimize welding properties.
Improved welding properties are achieved, the resistance during welding is reduced, the selection range of welding current is expanded, and the reliability of the process is improved.
Smart Images

Figure BDA0005200364670000031 
Figure BDA0005200364670000101 
Figure BDA0005200364670000201
Abstract
Description
[0001] The invention relates to a profiled sheet metal part having improved properties and to a method for producing such a profiled sheet metal part from a flat steel product.
[0002] When "flat steel products" or "sheet metal products" are discussed below, this refers to rolled products such as steel strips or steel plates from which "sheet metal blanks" (also called blanks) are cut out for producing, for example, body parts. "Formed sheet metal parts" or "sheet metal parts" of the type according to the invention have been produced from such sheet metal blanks; the terms "formed sheet metal parts" and "sheet metal parts" are used synonymously here.
[0003] Unless expressly stated otherwise, all figures relating to the contents of steel compositions reported in this application are based on weight. Therefore, all ambiguous percentage figures relating to steel alloys should be considered as figures in "% by weight". The figures given in this text for the contents of atmosphere components are based on volume (reported in "% by volume").
[0004] WO 2022 / 048990 A1 and EP 2 993 248 B1 disclose formed sheet metal parts with similar aluminum-based coatings and processes for their production.
[0005] Although such aluminum-based coatings significantly improve the further processability of hot-formed sheet metal parts, further technical challenges still exist in the downstream process steps. Aluminum is actually a self-passivating material that automatically limits the growth of the oxide layer.
[0006] However, especially at high temperatures, even in the case of aluminum surfaces, a natural oxide layer forms which cannot be ignored from a technological point of view. As a result, in particular making connections (for example by means of resistance spot welding methods) can be problematic, since the increased volume resistance in the presence of such an oxide layer impairs the connection. This makes it necessary to carefully select the required welding current depending on the specific material composite, which results in a limited overall welding range and therefore a low level of process reliability.
[0007] It is therefore an object of the present invention to match the composition and production parameters of the coating to one another in order to achieve improved welding properties.
[0008] This object is achieved by a formed sheet metal part, the formed sheet metal part comprising:
[0009] a steel matrix consisting of a steel containing 0.1 to 3 wt. % Mn and optionally up to 0.01 wt. % B, and
[0010] An aluminum-based anti-corrosion coating is disposed on at least one side of a steel substrate.
[0011] The anti-corrosion coating has an Al-based layer and an alloy layer, wherein the alloy layer is located above the steel substrate and the aluminum-based layer is located above the alloy layer. The alloy layer is composed of: 35 wt% to 90 wt% Fe, 2 wt% to 12 wt% Si, optionally up to 3 wt% alkali metals or alkaline earth metals, and optional other components whose content is limited to not more than 2.0 wt% in total, and the balance is aluminum. The Al-based layer is composed of: 35 wt% to 55 wt% Fe, 4 wt% to 10 wt% Si, optionally up to 3 wt% alkali metals or alkaline earth metals, and optional other components whose content is limited to not more than 2.0 wt% in total, and the balance is aluminum. In addition, the area-based impedance Z of the formed sheet metal part Α Not more than 1.0Ωcm 2 .
[0012] The optional content of up to 3% by weight of alkali metals or alkaline earth metals means that alkali metals and / or alkaline earth metals may be present, wherein the total content of all alkali metals and alkaline earth metals is up to 3% by weight.
[0013] Preferably, the optional content of alkali metal or alkaline earth metal in the alloy layer is composed of up to 0.5% by weight of Mg, and / or the optional content of alkali metal and alkaline earth metal in the Al-based layer is composed of up to 0.5% by weight of Mg. This means that the alloy layer is preferably composed of: 35% by weight to 90% by weight of Fe, 2% by weight to 12% by weight of Si, optionally up to 0.5% by weight of Mg and optional other components whose content is limited to not more than 2.0% by weight overall, and the balance is aluminum. The Al-based layer is preferably composed of: 35% by weight to 55% by weight of Fe, 4% by weight to 10% by weight of Si, optionally up to 0.5% by weight of Mg, and optional other components whose content is limited to not more than 2.0% by weight overall, and the balance is aluminum.
[0014] The impedance is determined as follows: two molded sheet metal parts, which are two-dimensionally coated on both sides, are pressed together with the help of two gold-plated copper electrodes, wherein the contact area of the two copper electrodes is area A, and the contact area of the two molded sheet metal parts is at least twice the contact area of the copper electrodes (i.e., the contact area of the two molded sheet metal parts is at least 2*A). The two copper electrodes are circular and have a diameter of 45 mm. The area-based impedance is mainly determined by the flow of current in the area directly between the two copper electrodes and to a lesser extent by the current in the surroundings of the copper electrodes. Because the contact area of the two molded sheet metal parts is at least twice the size of the contact area of the copper electrodes, it can be ensured that the current in the surroundings of the copper electrodes is not affected by the edge field lines of the sample. In addition, measurements have shown that at typical thicknesses of molded sheet metal parts (0.5 mm to 4 mm), the measured value does not depend on the plate thickness because the resistance is mainly determined by the contact area.
[0015] For the measurement, the formed sheet metal must have full contact over this area. In the simplest case of flat samples of formed sheet metal, these samples must therefore be plane-parallel. In the measurement, the samples of the formed sheet metal are pressed against each other in order to produce a conductive contact over the entire area. In practice, 3 kN has been found to be suitable here. An alternating voltage with an amplitude U of, for example, 10 mV and an average (polarization value) of about 0 V is applied to two copper electrodes. The frequency in the example described here is 10 mHz. Subsequently, the amplitude and phase shift of the resulting current I are measured. The area-based impedance is the ratio of the alternating voltage to the current multiplied by the area of the contact area:
[0016]
[0017] Impedance based on area does not exceed 1.0Ωcm 2 , especially not more than 0.9Ωcm 2 , preferably not more than 0.8Ωcm 2 , which has the advantage that a reliable or optimal connection can be made by resistance spot welding, in particular when there is a sufficient process window for selecting the welding current during the process. The amplitude of the phase shift between voltage and current does not exceed 3°, preferably does not exceed 1°, in particular does not exceed 0.1°. This has the advantage that what is effective and can be measured is essentially the ohmic fraction of the complex resistance.
[0018] The area-based impedance of a component is subject to various influences. In addition to the composition and thickness of the anti-corrosion coating, the surface characteristics also influence the impedance. For example, rough and uneven surfaces have the effect of reducing the size of the effective contact area. When two uneven surfaces are pressed against each other, this will inevitably result in effective contact areas that are truly adjacent to each other, as well as areas that remain a certain separation. The proportion of the effective contact area to the contact area has a significant influence on the impedance. It has been found that the production process described below leads to a layer composition and surface topology that has such a low impedance.
[0019] The described measurement method (impedance spectroscopy) is particularly suitable for determining the influence of surface structure and chemistry. In the literature, the suitability of welding is usually determined by cold transfer resistance. However, this is done using a relatively high direct current of 10A, and the resistance is determined only after the current flows for 15 seconds. However, due to such a high current, any factor that affects the impedance due to, for example, oxides on the surface can no longer be fully measured by at least partially decomposing it. However, it has been found in practice that these oxides in particular may cause problems in welding operations. Similarly, relatively high measurement currents may also cause surface melting and thus change the surface structure. Through the test method described here, the influence of surface properties can be quantified without any significant influence on the properties to be measured by the test method. In addition, in the conventional measurement of cold transfer resistance, a ball electrode with a diameter of 16mm is used. Due to the spherical shape, the diameter of the contact area of the electrode and the metal plate is therefore about 2mm to 5mm. In contrast, in the test method described here, a relatively large area of a planar electrode with a diameter of approximately 45mm is used. This increased area can also improve the detectability of surface properties (especially, for example, problematic oxides).
[0020] This formed sheet metal part is produced with the help of a specific coating and forming method. This production method of the present invention comprises the following steps:
[0021] a) providing a slab or thin slab consisting of a steel containing 0.1 to 3 wt. % Mn and optionally up to 0.01 wt. % B;
[0022] b) penetratingly heating the slab or thin slab at a temperature (T1) of 1100° C. to 1400° C.;
[0023] c) optionally, pre-rolling the through-heated slab or thin slab to obtain an intermediate product having an intermediate product temperature (T2) of 1000° C. to 1200° C.;
[0024] d) hot rolling to obtain a hot rolled flat steel product, wherein the final rolling temperature (T3) is 750° C. to 1000° C.;
[0025] e) optionally, coiling the hot rolled flat steel product, wherein the coiling temperature (T4) is not more than 700° C.;
[0026] f) descaling the hot rolled flat steel product;
[0027] g) optionally, cold rolling the flat steel product, wherein the degree of cold rolling is at least 30%;
[0028] h) annealing the flat steel product at an annealing temperature (T5) of 650° C. to 900° C. in an atmosphere consisting of 2% to 15% by volume of hydrogen, the balance being nitrogen and unavoidable impurities, and having a dew point of -50° C. to 25° C.;
[0029] i) cooling the flat steel product to an immersion temperature (T6) of 650° C. to 800° C., preferably 670° C. to 800° C.;
[0030] j) applying an anti-corrosion coating to the flat steel product which has been cooled to the immersion temperature by hot-dip coating in a melt bath having a melt temperature (T7) of 660° C. to 800° C., preferably 680° C. to 740° C., wherein the melt in the melt bath consists of 5% to 15% by weight of Si, optionally 2% to 4% by weight of Fe, optionally up to 3% by weight of alkali metals or alkaline earth metals, and optionally other components whose content is limited to not more than 2.0% by weight in total, the remainder being aluminum;
[0031] k) cooling the coated flat steel product to room temperature in an atmosphere containing 16% to 25% by volume of oxygen and having a dew point of -5°C to 25°C, wherein a first cooling period t in the temperature range of 600°C to 450°C MT The second cooling period t is longer than 10 seconds, in particular longer than 14 seconds, and is in the temperature range of 400° C. to 300° C. LT is more than 8 seconds, in particular more than 12 seconds;
[0032] 1) optionally, subjecting the coated flat steel product to skin pass rolling;
[0033] m) optionally, winding the coated flat steel product into a coil with a tension of 500 daN to 5000 daN;
[0034] n) separating sheet metal blanks from coated flat steel products;
[0035] o) heating the sheet metal blank so that the AC3 temperature of the blank is exceeded at least to some extent and the temperature T of the blank when inserted into the forming tool provided for the hot press forming operation is ins at least partially at a temperature above Ms+100° C., wherein Ms represents the martensite start temperature;
[0036] p) Inserting the heated sheet metal blank into the forming tool, wherein the transfer time t required for removing the blank from the heating device and inserting the blank is trans No more than 20 seconds, preferably no more than 15 seconds;
[0037] q) hot press forming the sheet metal blank into a formed sheet metal part, wherein during the hot press forming process the blank is subjected to a period t exceeding 1 second. toolThe cooling rate r at least partially exceeds 30 K / s tool Cool to target temperature T target , and optionally maintained at that temperature;
[0038] r) removing the molded product that has cooled to the target temperature T from the tool target Formed sheet metal parts.
[0039] In step a), a semi-finished product of the alloy composition defined according to the invention for a flat steel product is provided. This can be a slab produced by conventional continuous slab casting or by continuous thin slab casting.
[0040] In step b), the semi-finished product is through-heated at a temperature (T1) of 1100° C. to 1400° C. If the semi-finished product is to be cooled after casting, the semi-finished product is first reheated to 1100° C. to 1400° C. for through-heating. The through-heating temperature should be at least 1100° C. to ensure good formability in the subsequent rolling process. The through-heating temperature should not exceed 1400° C. to avoid molten phase portions in the semi-finished product.
[0041] In an optional step c), the semi-finished product is pre-rolled into an intermediate product. Thin slabs are usually not subjected to any pre-rolling. If necessary, thick slabs to be rolled into hot-rolled strip can be pre-rolled. In this case, the temperature of the intermediate product (T2) at the end of pre-rolling should be at least 1000° C., so that the intermediate product contains sufficient heat for the subsequent finishing step. However, high rolling temperatures also promote grain growth during the rolling operation, which has an adverse effect on the mechanical properties of the flat steel product. In order to minimize grain growth during the rolling operation, the temperature of the intermediate product at the end of pre-rolling should not exceed 1200° C.
[0042] In step d), the slab or thin slab, or the rolled intermediate product (if step c) has been carried out) is rolled to obtain a hot-rolled flat steel product. If step c) has been carried out, the intermediate product is usually finished rolled immediately after pre-rolling. Finishing rolling usually starts no later than 90 seconds after the end of pre-rolling. At the final rolling temperature (T3), the slab, thin slab or intermediate product (if step c) has been carried out) is rolled to completion. The final rolling temperature, i.e. the temperature of the completely hot-rolled flat steel product at the end of the hot rolling operation, is 750°C to 1000°C. In the case of a final rolling temperature below 750°C, the amount of free vanadium is reduced due to the precipitation of relatively large amounts of vanadium carbides. The vanadium carbides precipitated during the finishing rolling process are very large. They usually have an average grain size of 30nm or more and are no longer dissolved in a subsequent annealing process (for example, an annealing process carried out before hot dip coating). The final rolling temperature is limited to a value not exceeding 1000°C to prevent coarsening of the austenite grains. Furthermore, it is relevant for process-technical purposes that the final rolling temperature does not exceed 1000°C in order to establish a coiling temperature (T4) below 700°C.
[0043] The hot rolling of the flat steel product can be carried out in the form of a continuous hot strip rolling operation or a reverse rolling operation. In the case of continuous hot strip rolling, step e) provides for optional coiling of the hot rolled flat steel product. For this purpose, the hot rolled strip after hot rolling is cooled to the coiling temperature (T4) in less than 50 seconds. The cooling medium used for this purpose can be, for example, water, air or a combination of the two. The coiling temperature (T4) should not exceed 700°C to avoid the formation of large vanadium carbides. In principle, there is no lower limit to the coiling temperature. However, it has been found that a coiling temperature of at least 500°C is beneficial to cold rolling properties. Subsequently, the coiled hot rolled strip is cooled to room temperature in air in a conventional manner.
[0044] In step f), the hot rolled flat steel product is descaled in a conventional manner by pickling or other suitable treatment.
[0045] Prior to the annealing treatment in step g), the descaled hot-rolled flat steel product can optionally be cold-rolled, for example, to meet higher requirements on the thickness tolerance of the flat steel product. The degree of cold rolling (DCR) should be at least 30% in order to introduce sufficient deformation energy into the flat steel product for rapid recrystallization. The degree of cold rolling DCR is understood to be the quotient of the reduction in cold-rolled thickness ΔDCR divided by the hot-rolled strip thickness d:
[0046] DCR=ΔdCR / d
[0047] ΔdCR=thickness reduction during cold rolling (unit: mm), d=thickness of hot-rolled strip (unit: mm), wherein the thickness reduction ΔdCR is calculated based on the difference in thickness of the flat steel product before cold rolling relative to the thickness of the flat steel product after cold rolling. The flat steel product before cold rolling is usually a hot-rolled strip with a hot-rolled strip thickness d. The flat steel product after cold rolling is also often referred to as cold-rolled strip. The degree of cold rolling can in principle assume very high values of more than 90%. However, it has been found that a degree of cold rolling not exceeding 80% is advantageous for avoiding strip cracks.
[0048] In step h), the flat steel product is annealed at an annealing temperature (T5) of 650° C. to 900° C. For this purpose, the flat steel product is first heated to the annealing temperature within 10 seconds to 120 seconds and then kept at the annealing temperature for 30 seconds to 600 seconds. The annealing temperature is at least 650° C., preferably at least 720° C. For economic reasons, annealing temperatures above 900° C. are undesirable.
[0049] The annealing in step h) is carried out in an atmosphere consisting to some extent of 2% to 15% by volume of hydrogen, preferably 2% to 10% by volume of hydrogen, in particular 2% to 4% by volume of hydrogen, the remainder being nitrogen and unavoidable impurities. The dew point during the annealing is between -50°C and 25°C. Preferably, the dew point is greater than 0°C, preferably greater than 4°C. This low oxygen atmosphere in combination with the established dew point ensures that the formation of the oxide layer is sufficiently limited to achieve the desired surface topology, which leads to the specific impedance of the present invention.
[0050] In step i), after annealing, the flat steel product is cooled to an immersion temperature (T6) in order to prepare for the subsequent coating process. The immersion temperature is lower than the annealing temperature and is matched to the temperature of the melt bath. The immersion temperature is 600° C. to 800° C., preferably at least 650° C., more preferably at least 670° C., and more preferably at most 700° C.
[0051] In order to form a particularly uniform interface layer, it is important that there is sufficient thermal energy in the interface layer between the steel substrate and the aluminum melt. This is not the case at temperatures below 600° C., so that undesirable compounds may form, whose subsequent reconversion may produce pores. Above the preferred immersion temperature, the diffusion rate of iron into the aluminum increases significantly, so that even at the beginning of the coating process, more iron can diffuse into the still liquid interface layer. The duration of cooling of the annealed flat steel product from the annealing temperature T5 to the immersion temperature T6 is preferably 10 seconds to 180 seconds. In particular, the immersion temperature T6 differs from the temperature of the melt bath T7 by no more than 30 K, in particular by no more than 20 K, preferably by no more than 10 K.
[0052] In step j), the flat steel product is subjected to coating treatment. The coating treatment is preferably achieved by continuous hot dip coating. The coating can be applied only to one side, both sides or all sides of the flat steel product. "Both sides of the flat steel product" refers to two relatively large faces of the flat steel product. The narrow face is called the edge. The coating treatment is preferably carried out in a hot dip coating process, especially in a continuous process. The flat steel product is usually in contact with the melt bath on all sides, so that all sides are coated. The temperature (T7) of the melt bath containing the alloy to be applied to the flat steel product in liquid form is usually 660°C to 800°C, preferably 680°C to 740°C. It has been found that aluminum-based alloys are particularly suitable for coating anti-corrosion coatings on aging-resistant flat steel products. In this case, the melt bath contains 5% to 15% by weight of Si, optionally 2% to 4% by weight of Fe, optionally up to 3% by weight of alkali metals or alkaline earth metals, and optional other components with a total content limited to no more than 2.0% by weight, and the balance is aluminum. In a preferred variant, the Si content of the melt is 7% to 12% by weight, in particular 8% to 10% by weight. In a preferred variant, the optional content of alkali metal or alkaline earth metal in the melt comprises 0.1% to 1.0% by weight of Mg, in particular 0.1% to 0.7% by weight of Mg, preferably 0.1% to 0.5% by weight of Mg. In addition, the optional content of alkali metal or alkaline earth metal in the melt may in particular comprise at least 0.0015% by weight of Ca, in particular at least 0.01% by weight of Ca. More preferably, the optional content of alkali metal or alkaline earth metal in the melt consists of 0.1% to 1.0% by weight of Mg, in particular 0.1% to 0.7% by weight of Mg, preferably 0.1% to 0.5% by weight of Mg, and optionally at least 0.0015% by weight of Ca, in particular at least 0.01% by weight of Ca. In a preferred variant, the optional content of alkali metal or alkaline earth metal consists of up to 0.5% by weight of Mg.
[0053] After the coating treatment, the coated flat steel product is cooled to room temperature in step k). The first cooling period t in the temperature range of 600° C. to 450° C. (medium temperature range MT) MT The second cooling period t is longer than 10 seconds, in particular longer than 14 seconds, in the temperature range of 400° C. to 300° C. (low temperature range LT). LT More than 8 seconds, especially more than 12 seconds.
[0054] The cooling is carried out in an atmosphere containing 16 to 25% by volume of oxygen, preferably 18 to 22% by volume of oxygen, in particular in ambient air, and a dew point of -5° C. to 25° C. This involves both cooling in the medium temperature range and cooling in the low temperature range.
[0055] The first cooling period t in the temperature range of 600°C to 450°C (medium temperature range MT)MT This can be achieved by gradual, continuous cooling or by holding the temperature in this temperature range for a certain period of time. Even intermediate heating is possible. It is important that the flat steel product is kept in a temperature range of 600°C to 450°C for at least the cooling period t MT In this temperature range, on the one hand, the diffusion rate of iron into aluminum is significant, and on the other hand, the diffusion of aluminum into steel is suppressed because the temperature is below half the melting temperature of steel. This allows iron to diffuse into the anti-corrosion coating, while aluminum does not diffuse significantly into the steel matrix.
[0056] Diffusion of iron into the corrosion protection coating has several advantages.
[0057] Firstly, austenitization delays the melting of the corrosion protection coating before press hardening (see below). Secondly, the thermal expansion coefficients of the corrosion protection coating and the substrate are homogenized. This means that the transition zone between the thermal expansion coefficient of the substrate and the thermal expansion coefficient of the surface is widened, which reduces thermal stresses during reheating.
[0058] At the same time, the diffusion of aluminum into the steel matrix has considerable disadvantages.
[0059] Since aluminum has a very high affinity for nitrogen, a high aluminum content can have the effect of removing nitrogen from fine precipitates such as niobium carbonitride or titanium carbonitride, and instead preferentially forming coarse precipitates such as aluminum nitride at the grain boundaries. This will deteriorate the collision performance and reduce the bending angle. In addition, this will destroy the stability of fine precipitates (such as niobium-containing precipitates) in the uppermost matrix region, which are important for many preferred properties. In addition, the uneven diffusion rate of aluminum into ferrite in the steel matrix compared to pearlite / bainite / martensite will lead to an uneven distribution of Al in the edge layer of the steel matrix. In order to improve the collision performance and bending performance, this situation should also be avoided. Therefore, these disadvantages of aluminum diffusion into the steel matrix are reduced or avoided by inhibition.
[0060] Since the preferred first cooling time t MT (14 seconds), the iron concentration in the interfacial transition layer increases to such an extent that this further reduces the activity of the aluminum in the coating directly at the substrate boundary. This leads to a further reduction in the absorption of aluminum into the substrate during austenitization before die hardening, with the associated advantages mentioned above.
[0061] The second cooling period t in the temperature range of 400°C to 300°C (low temperature range LT) LT This can also be achieved by gradual, continuous cooling or by holding the temperature in this temperature range for a certain period of time. Even intermediate heating is possible. It is important that the flat steel product is kept at a temperature range of 400°C to 300°C for at least the cooling period t LT Length of time.
[0062] In this temperature range, carbon still has a certain diffusion rate in the steel matrix, while the thermodynamic solubility is very low. Therefore, carbon diffuses to lattice defects (such as dissolved Nb atoms) and accumulates there. Due to their much higher atomic volume, these widen the atomic lattice, thereby increasing the size of the tetrahedral and octahedral gaps in the atomic lattice, so that the local solubility of C increases. This causes the clusters of C and Nb to be converted into very fine precipitates during the austenitizing step of hot forming, and leads to the refinement of the austenite microstructure, which also leads to a hardened microstructure and reduces the free hydrogen content.
[0063] In the case of preferred holding times of more than 12 seconds, very fine iron carbides (called transition carbides) are additionally formed, which then dissolve rapidly during austenitization, leading to additional austenite seeds and thus to a finer austenite microstructure and thus also to a hardened microstructure.
[0064] In order to improve the surface roughness of the flat steel product, the coated flat steel product can optionally be subjected to a skin-pass rolling operation, the degree of skin-pass rolling being up to 2%.
[0065] In the subsequent step m), the coated flat steel product is wound into a coil so that it can be stored or transported. The coiling is carried out with a tension of at least 500 daN (decade Newtons). The tension is preferably not more than 5000 daN, in particular not more than 1500 daN.
[0066] Subsequently, in step n), the sheet metal blanks are separated from the coated flat steel product and further processed.
[0067] The sheet metal blank itself is then heated in a known manner (step o) so that the Ac3 temperature of the blank is exceeded at least to a certain extent. In particular, the temperature is at least partially between Ac3 and 1000° C., preferably between 850° C. and 950° C. In addition, the temperature T of the blank when it is inserted into the forming tool provided for the hot press forming operation (step p)) is ins At least partly at a temperature higher than Ms+100° C., in particular higher than Ms+300° C. In particular, the temperature of the blank during insertion T ins At least partially 600° C. In a particularly preferred variant, the temperature of the blank during insertion T insAt least partially, in particular completely, in the range of 600°C to 850°C to ensure good formability and sufficient hardenability. In the context of the present application, "partially exceeding the temperature" (here AC3 or Ms+100°C or 600°C) means that at least 30% of the blank volume, in particular at least 60%, preferably the entire blank exceeds the corresponding temperature. This also applies to the at least partial presence of temperatures in the range of 600°C to 850°C in the above-mentioned preferred variants. Therefore, at least 30% of the blank has an austenitic microstructure when inserted into the forming tool, which means that the transition from ferrite to an austenitic microstructure does not need to be completed when inserted into the forming die. On the contrary, at most 70% of the blank volume may consist of other microstructural components, such as annealed bainite, annealed martensite and / or non-recrystallized or partially recrystallized ferrite when inserted into the forming tool. For this purpose, during the heating process, specific areas of the blank can be kept at a lower temperature level than other areas. For this purpose, the supply of heat can be directed exclusively only to certain parts of the blank, or the parts to be heated to a lower degree can be shielded from the supply of heat. In the parts of the blank in which the temperature is kept lower, only a significantly smaller amount of martensite (if any) is formed during the forming process in the tool, so that the microstructure there is much softer than in the respective other parts with a martensitic microstructure. In this way, in the respectively formed shaped sheet metal, softer areas can be established exclusively in which, for example, the toughness is optimal for the respective end use, while other areas of the shaped sheet metal have maximized strength.
[0068] Since the temperature reached in the sheet metal blank is at least to a certain extent Ac3 to 1000°C, preferably 850°C to 950°C, the maximum strength properties of the resulting formed sheet metal part can be achieved.
[0069] The minimum temperature Ac3 to be exceeded is determined by the following formula specified by HOUGARDY, HP in Werkstofkunde Stahl, Band 1: Grundlagen [Materials; Steels; Volume 1: Principles], Verlag Stahleisen GmbH, Düsseldorf, 1984, p. 229:
[0070] Ac3 = (902 wt% - 225*%C + 19*%Si - 11*%Mn - 5*%Cr + 13*%Mo - 20*%Ni + 55*%V) [°C / wt%]
[0071] Wherein %C = the corresponding C content of the steel constituting the blank, %Si = the corresponding Si content of the steel constituting the blank, %Mn = the corresponding Mn content of the steel constituting the blank, %Cr = the corresponding Cr content of the steel constituting the blank, %Mo = the corresponding Mo content of the steel constituting the blank, %Ni = the corresponding Ni content of the steel constituting the blank, and %V = the corresponding V content of the steel constituting the blank.
[0072] Since the blank is completely heated through in step o), an optimal uniform distribution of properties can be achieved.
[0073] In a preferred embodiment variant, the average heating rate r of the sheet metal blank during heating in step o) is furnace is at least 3 K / s, preferably at least 5 K / s, in particular at least 6 K / s, preferably at least 8 K / s, in particular at least 10 K / s, preferably at least 15 K / s. The average heating rate r furnace is the average heating rate from 30°C to 700°C.
[0074] In a preferred embodiment, the normalized average heating θ norm It is at least 5 Kmm / s, in particular at least 8 Kmm / s, preferably at least 10 Kmm / s. The normalized average heating is a maximum of 15 Kmm / s, in particular at most 14 Kmm / s, preferably at most 13 Kmm / s.
[0075] Average heating θ is the product of the average heating rate from 30°C to 700°C (in Kelvin per second) and the plate thickness (in millimeters).
[0076] For normalized average heating, the product Θ is calculated by the current furnace temperature T furnace Relative to the reference furnace temperature T furnace,reference Normalize to 900℃=1173.15K as follows:
[0077]
[0078] In each case the furnace temperature shall be stated in Kelvin.
[0079] In a preferred embodiment, heating is carried out at a furnace temperature T furnace The temperature of the reaction mixture is at least Ac3+10K, preferably at least 850°C, preferably at least 880°C, more preferably at least 900°C, especially at least 920°C and not more than 1000°C, preferably not more than 950°C, more preferably not more than 930°C.
[0080] Preferably, the dew point of the furnace atmosphere in the furnace here is at least -20°C, preferably at least -15°C, more preferably at least -10°C, especially at least -5°C, more preferably at least 0°C, and does not exceed +25°C, preferably does not exceed +20°C, especially does not exceed +15°C, preferably does not exceed +10°C, especially does not exceed +5°C.
[0081] In a particular embodiment, the heating in step o) is carried out stepwise in zones of different temperatures. In particular, the heating is carried out in a roller hearth furnace with different heating zones. The heating is carried out in a first heating zone having a temperature (referred to as the furnace inlet temperature) of at least 650° C., preferably at least 680° C., in particular at least 720° C. The temperature of the first heating zone preferably does not exceed 900° C., in particular does not exceed 850° C. More preferably, the maximum temperature of all heating zones in the furnace does not exceed 1200° C., in particular does not exceed 1000° C., preferably does not exceed 950° C., and more preferably does not exceed 930° C.
[0082] In both variants (constant furnace temperature, step-wise heating), the total time in the furnace, t, consisting of the heating time and the holding time furnace Preferably at least 2 minutes, especially at least 3 minutes, preferably at least 4 minutes. In addition, in both variants, the total time in the furnace is preferably no more than 20 minutes, especially no more than 15 minutes, preferably no more than 12 minutes, especially no more than 8 minutes. The advantage of the extended total time in the furnace is that a uniform austenitization of the sheet metal blank is guaranteed. On the other hand, a long time above Ac3 will lead to grain coarsening, which has an adverse effect on mechanical properties.
[0083] The blank, which has been heated in this way, is taken out of a corresponding heating device, for example, which can be a conventional heating furnace, an induction heating device known per se, or a conventional device for keeping the formed sheet metal at a high temperature, and is conveyed to the forming tool at a sufficient speed so that the temperature when it reaches the tool is at least partially higher than Ms+100°C, in particular higher than Ms+300°C, preferably higher than 600°C, in particular higher than 650°C, and more preferably higher than 700°C. In particularly preferred variants, the temperature is at least partially higher than the AC1 temperature. In all these variants, the temperature does not exceed 900°C in particular. These temperature ranges ensure good formability of the material as a whole.
[0084] In step p), the austenitized blank is preferably transferred from the respective heating device used to the forming tool in no more than 20 seconds, in particular no more than 15 seconds. Such rapid transport is required to avoid excessive cooling before forming.
[0085] The tool is usually at a temperature of between room temperature (RT) and 200° C., preferably between 20° C. and 180° C., in particular between 50° C. and 150° C., when inserting the blank. If, for example, the cooling water used is slightly colder (e.g. 15° C.), the tool temperature when inserting the blank may also be slightly below room temperature. This means that the tool temperature in the various embodiments is between 10° C. and 200° C. when inserting the blank. The residence time in the tool t tool Preferably at least 2 seconds, especially at least 3 seconds, more preferably at least 5 seconds. The residence time in the tool is preferably not more than 25 seconds, especially not more than 20 seconds, preferably not more than 10 seconds.
[0086] Target temperature T of formed sheet metal target To a certain extent, it is at least below 400°C, preferably below 300°C, especially below 250°C, preferably below 200°C, more preferably below 180°C, especially below 150°C. Alternatively, the target temperature T of the formed sheet metal part target More preferably, it is less than Ms-50°C, wherein Ms represents the martensite start temperature. In addition, the target temperature of the formed sheet metal is preferably at least 20°C, more preferably at least 50°C.
[0087] The martensite starting temperature of steel within the specified range of the present invention should be calculated by the following formula
[0088] Ms[℃]=(490.85wt%-302.6%C-30.6%Mn-16.6%Ni-8.9%Cr+2.4%Mo-11.3%Cu+8.58%Co+7.4%W-14.5%Si)[℃ / wt%]
[0089] Wherein %C here represents the C content of the corresponding steel, %Mn represents the Mn content of the corresponding steel, %Mo represents the Mo content of the corresponding steel, %Cr represents the Cr content of the corresponding steel, %Ni represents the Ni content of the corresponding steel, %Cu represents the Cu content of the corresponding steel, %Co represents the Co content of the corresponding steel, %W represents the W content of the corresponding steel, and %Si represents the Si content of the corresponding steel, all of which are measured in weight %.
[0090] The AC1 temperature and AC3 temperature of steel within the specified range of the present invention should be calculated by the following formula
[0091] AC1[°C]=(739 wt%-22*%C-7*%Mn+2*%Si+14*%Cr+13*%Mo-13*%Ni+20*%V)[°C / wt%]
[0092] and
[0093] AC3[℃]=(902wt%-225*%C+19*%Si-11*%Mn-5*%Cr+13*%Mo-20*%Ni+55*%V)[℃ / wt%]
[0094] Here, too, %C represents the C content of the corresponding steel, %Si represents the Si content of the corresponding steel, %Mn represents the Mn content of the corresponding steel, %Cr represents the Cr content of the corresponding steel, %Mo represents the Mo content of the corresponding steel, %Ni represents the Ni content of the corresponding steel, and %V represents the vanadium content of the corresponding steel (Brandis H 1975TEW-Techn.Ber.1 8-10).
[0095] Therefore, in this tool, the blank is not only formed into a formed sheet metal part, but is also quenched to the target temperature at the same time. The rate of cooling to the target temperature in the tool r tool In particular, it is at least 20 K / s, preferably at least 30 K / s, in particular at least 50 K / s, in a specific embodiment at least 100 K / s.
[0096] After the formed sheet metal part is removed in step r), a cooling time t of 0.5 to 600 seconds is AB The formed sheet metal is cooled to a cooling temperature T below 100°C. AB This is usually achieved by air cooling.
[0097] The steel used in the method comprises 0.1 to 3 wt. % Mn and optionally up to 0.01 wt. % B. The same applies to the steel for the profiled sheet metal part. The preferred steel compositions described below should be regarded as preferred both for the profiled sheet metal part and for the method for its production.
[0098] In particular, the microstructure of the steel can be converted into a martensitic microstructure or a partially martensitic microstructure by hot forming. Therefore, the microstructure of the steel matrix of the formed sheet metal part is preferably a martensitic microstructure or an at least partially martensitic microstructure, because this has a particularly high hardness.
[0099] The steel matrix is more preferably a steel consisting of iron and unavoidable impurities and the following (in wt%):
[0100] C: 0.04 wt% to 0.45 wt%,
[0101] Si: 0.02 wt% to 1.2 wt%,
[0102] Mn: 0.5 wt% to 2.6 wt%,
[0103] Al: 0.02 wt% to 1.0 wt%,
[0104] P: ≤0.05% by weight
[0105] S: ≤0.02% by weight
[0106] N: ≤0.02% by weight
[0107] Sn: ≤ 0.03 wt%
[0108] As: ≤ 0.01 wt%
[0109] Ca: ≤ 0.005 wt%
[0110] and optionally one or more of the elements Cr, B, Mo, Ni, Cu, Nb, Ti, V in the following contents:
[0111] Cr: 0.08 wt% to 1.0 wt%,
[0112] B: 0.001 wt% to 0.005 wt%
[0113] Mo: ≤ 0.5 wt%
[0114] Ni: ≤ 0.5 wt%
[0115] Cu: ≤ 0.2 wt%
[0116] Nb: 0.02 wt% to 0.08 wt%,
[0117] Ti: 0.01 wt% to 0.08 wt%
[0118] V: ≤ 0.1 wt%.
[0119] The elements P, S, N, Sn, As, and Ca are impurities that cannot be completely avoided in steelmaking. In addition to these elements, other elements may also be present in the steel as impurities. These other elements are collectively referred to as "inevitable impurities". The content of inevitable impurities preferably does not exceed 0.2% by weight, preferably not more than 0.1% by weight. The optional alloying components Cr, B, Nb, and Ti reported with lower limits may also appear as inevitable impurities in the steel matrix in a content below the corresponding lower limit. In this case, they are also counted as inevitable impurities, and their total content is limited to not more than 0.2% by weight, preferably not more than 0.1% by weight. The respective upper limits of the corresponding contamination of these elements are as follows:
[0120] Cr: ≤0.050% by weight
[0121] B: ≤0.0005 wt%
[0122] Nb: ≤ 0.005 wt%,
[0123] Ti: ≤ 0.005% by weight
[0124] These preferred upper limits should be considered alternatively or together. Therefore, preferred variants of steel meet one or more of these four conditions.
[0125] In a preferred embodiment, the steel has a C content of no more than 0.37 wt. % and / or at least 0.06 wt. %. In particularly preferred execution variants, the C content is in the range of 0.06 wt. % to 0.09 wt. %, or in the range of 0.12 wt. % to 0.25 wt. %, or in the range of 0.33 wt. % to 0.37 wt. %.
[0126] In a preferred embodiment, the Si content of the steel is not more than 1.00 wt. % and / or at least 0.06 wt. %.
[0127] In preferred embodiments, the steel has a Mn content of no more than 2.4% by weight and / or at least 0.75% by weight. In particularly preferred embodiments, the Mn content is in the range of 0.75% by weight to 0.85% by weight or in the range of 1.0% by weight to 1.6% by weight.
[0128] In a preferred variant, the Al content of the steel is not more than 0.75% by weight, in particular not more than 0.5% by weight, preferably not more than 0.25% by weight. Alternatively or additionally, the Al content is preferably at least 0.02% by weight.
[0129] In addition, it has been found that this may be helpful when the sum of the contents of silicon and aluminum is limited. In a preferred variant, the sum of the contents of Si and Al (generally referred to as Si+Al) is therefore no more than 1.5% by weight, preferably no more than 1.2% by weight. In addition or alternatively, the sum of the contents of Si and Al is at least 0.06% by weight, preferably at least 0.08% by weight.
[0130] The elements P, S and N are typical impurities that cannot be completely avoided in steelmaking. In a preferred variant, the P content is not more than 0.03% by weight. Independently of this, the S content is preferably not more than 0.012%. In addition or as a supplement, the N content is preferably not more than 0.009% by weight.
[0131] Optionally, the steel further contains chromium in an amount of 0.08% to 1.0% by weight. The Cr content preferably does not exceed 0.75% by weight, in particular does not exceed 0.5% by weight.
[0132] In the case of the optional presence of chromium in the alloy, the sum of the chromium and manganese contents is preferably limited to no more than 3.3% by weight, in particular no more than 3.15% by weight. In addition, the sum is at least 0.5% by weight, preferably at least 0.75% by weight.
[0133] Preferably, the steel optionally additionally contains boron in an amount of 0.001 to 0.005% by weight. In particular, the B content is not more than 0.004% by weight.
[0134] Optionally, the steel may contain molybdenum in an amount of not more than 0.5% by weight, in particular not more than 0.1% by weight.
[0135] In addition, the steel may optionally contain nickel in an amount of not more than 0.5% by weight, preferably not more than 0.15% by weight.
[0136] Optionally, the steel may additionally contain copper in an amount of not more than 0.2% by weight, preferably not more than 0.15% by weight.
[0137] In addition, the steel may optionally contain one or more of the microalloying elements Nb, Ti and V. Here, the optional Nb content is at least 0.02 wt.-% and at most 0.08 wt.-%, preferably at most 0.04 wt.-%. The optional Ti content is at least 0.01 wt.-% and at most 0.08 wt.-%, preferably at most 0.04 wt.-%. The optional V content is preferably not more than 0.1 wt.-%, preferably not more than 0.05 wt.-%.
[0138] When two or more of the elements Nb, Ti and V are optionally contained in the alloy, it is preferred to limit the sum of the contents of Nb, Ti and V. The sum is not more than 0.1% by weight, in particular not more than 0.068% by weight. In addition, the sum is preferably at least 0.015% by weight.
[0139] In a preferred variant, the anticorrosion coating of the cooled flat steel product obtained in step k) has an Al-based layer, whose chemical composition corresponds to the composition of the melt used in step j). This means that it is composed in particular of 5% to 15% by weight of Si, optionally 2% to 4% by weight of Fe, optionally up to 3% by weight of alkali metals or alkaline earth metals, and optional other components whose total content is limited to no more than 2.0% by weight, the remainder being aluminum. This is due to the diffusion of iron from the steel matrix into the liquid coating (outside the melt) in steps j) and k), so that the anticorrosion coating of the cooled flat steel product during solidification comprises in particular an alloy layer and an Al-based layer. In a preferred variant of the Al-based layer, the optional content of alkali metals or alkaline earth metals comprises 0.1% to 1.0% by weight of Mg, in particular 0.1% to 0.7% by weight of Mg, preferably 0.1% to 0.5% by weight of Mg. In addition, the optional content of alkali metals or alkaline earth metals in the Al-based layer may in particular comprise at least 0.0015% by weight of Ca, in particular at least 0.1% by weight of Ca. More preferably, the optional content of alkali metals or alkaline earth metals consists of 0.1 to 1.0 wt.-% Mg, especially 0.1 to 0.7 wt.-% Mg, preferably 0.1 to 0.5 wt.-% Mg, and optionally at least 0.0015 wt.-% Ca, especially at least 0.1 wt.-% Ca. More preferably, the optional content of alkali metals or alkaline earth metals consists of up to 0.5 wt.-% Mg.
[0140] The alloy layer is located above the steel substrate and directly adjacent to it. The alloy layer is basically formed by aluminum and iron. Other elements in the steel substrate or melt composition will not significantly accumulate in the alloy layer. The alloy layer is preferably composed of 35% by weight to 60% by weight of Fe, preferably α-iron, a content limited to a total amount of no more than 5.0% by weight, preferably 2.0% by weight of optional other components, the balance being aluminum, wherein the Al content preferably rises in the surface direction. The optional other components especially include other components of the melt (i.e., silicon and optional alkali metals or alkaline earth metals, especially Mg and Ca) and other components of the steel substrate except iron.
[0141] The Al-based layer is located above the alloy layer and directly adjacent to it. The composition of the Al-based layer preferably corresponds to the composition of the melt in the melt bath. This means that it is especially composed of 5 wt % to 15 wt % Si, optionally 2 wt % to 4 wt % Fe, optionally up to 3 wt % alkali metal or alkaline earth metal and the total content is limited to no more than 2.0 wt % of optional other components, the remainder being aluminum. The preferred composition of the Al-based layer corresponds to the preferred melt composition. In the preferred variant of the Al-based layer, the optional content of the alkali metal or alkaline earth metal includes 0.1 wt % to 1.0 wt % Mg, especially 0.1 wt % to 0.7 wt % Mg, preferably 0.1-0.5 wt % Mg. In addition, the optional content of the alkali metal or alkaline earth metal in the Al-based layer can especially include at least 0.0015 wt % Ca, especially at least 0.1 wt % Ca. More preferably, the optional content of alkali metals or alkaline earth metals consists of 0.1 to 1.0 wt.-% Mg, especially 0.1 to 0.7 wt.-% Mg, preferably 0.1 to 0.5 wt.-% Mg, and optionally at least 0.0015 wt.-% Ca, especially at least 0.1 wt.-% Ca. More preferably, the optional content of alkali metals or alkaline earth metals consists of up to 0.5 wt.-% Mg.
[0142] In another preferred variant of the anti-corrosion coating, the Si content in the alloy layer is lower than the silicon content in the Al base layer.
[0143] The thickness of the anticorrosion coating is preferably 5 μm to 60 μm, in particular 10 μm to 40 μm. In the case of a double-sided anticorrosion coating, the coating weight of the anticorrosion coating is in particular 30 Up to 360 or 15 in case of single-sided variant Up to 180 In the case of double-sided anti-corrosion coating, the coating weight of the anti-corrosion coating is preferably 100 Up to 200 or 50 in case of single-sided variant Up to 100 In the case of double-sided anti-corrosion coating, the coating weight of the anti-corrosion coating is more preferably 120 Up to 180 or 60 in case of single-sided variant to 90
[0144] The thickness of the alloy layer is preferably less than 20 μm, more preferably less than 16 μm, more preferably less than 12 μm, and especially less than 10 μm. The thickness of the Al-based layer is derived from the difference in thickness between the anticorrosion coating and the alloy layer. Even in the case of a thin anticorrosion coating, the thickness of the Al-based layer is preferably at least 1 μm.
[0145] In a preferred variant, the flat steel product comprises an oxide layer arranged above the anti-corrosion coating. The oxide layer is located in particular above the Al-based layer and preferably forms the outer end of the anti-corrosion coating.
[0146] The oxide layer consists in particular to a certain extent of more than 80% by weight of oxides, wherein the majority of the oxides (i.e. more than 50% by weight of oxides) are aluminum oxide. In addition to aluminum oxide, the oxide layer optionally contains hydroxides and / or oxides of alkali metals and alkaline earth metals (especially magnesium oxide), either alone or as a mixture. The remainder of the oxide layer, not counting oxides and optionally present hydroxides, preferably consists of silicon, aluminum, iron and / or magnesium in metallic form.
[0147] The oxide layer of the flat steel product preferably has a thickness of more than 50 nm. In particular, the thickness of the oxide layer does not exceed 500 nm.
[0148] When the flat steel product is reheated in step o), the iron diffuses further into the corrosion protection coating. Thus, even with a short heating time, a completely iron-alloyed corrosion protection coating is formed with an Fe content of at least 35% by weight.
[0149] The profiled sheet metal part according to the invention obtained in step r) also corresponds to the profiled sheet metal part claimed in claim 1 and preferably has the following features.
[0150] The anti-corrosion coating of the produced formed sheet metal part comprises an alloy layer and an Al-based layer.
[0151] The alloy layer here is located above the steel substrate and directly adjacent to it. The alloy layer of the formed sheet metal part is preferably composed of 35% by weight to 90% by weight of Fe, 2% by weight to 12% by weight of Si, optionally up to 3% by weight of alkali metal or alkaline earth metal, and optional other components whose content is limited to a total amount of no more than 2.0% by weight, and the balance is aluminum. Due to the further diffusion of iron into the alloy layer, the proportion of Si and alkali metal or alkaline earth metal (especially Mg in the preferred variant) is correspondingly lower than its corresponding proportion in the melt in the melt bath. The optional content of alkali metal or alkaline earth metal in the alloy layer is preferably composed of up to 0.5% by weight of Mg. The alloy layer preferably contains at least 0.1% by weight of Mg and up to 0.3% by weight of Mg.
[0152] The alloy layer preferably has a ferritic microstructure.
[0153] The Al-based layer of the formed sheet metal is located above and directly adjacent to the alloy layer of the formed sheet metal. The Al-based layer of the formed sheet metal is preferably composed of 35% to 55% by weight of Fe, 4% to 10% by weight of Si, optionally up to 3% by weight of alkali metal or alkaline earth metal, and optional other components whose content is limited to not more than 2.0% by weight in total, and the balance is aluminum. The optional content of alkali metal or alkaline earth metal in the Al-based layer is preferably composed of up to 0.5% by weight of Mg. The Al-based layer preferably contains at least 0.1% by weight of Mg and up to 0.3% by weight of Mg.
[0154] The Al-based layer may have a uniform element distribution, wherein the local element content varies by no more than 10%. In contrast, a preferred variant of the Al-based layer has a low-silicon phase and a silicon-rich phase. The low-silicon phase here refers to a region where the average Si content is at least 20% lower than the average Si content of the Al-based layer. The silicon-rich phase here refers to a region where the average Si content is at least 20% higher than the average Si content of the Al-based layer.
[0155] In a preferred variant, the silicon-rich phase is arranged in the silicon-low phase. In particular, the silicon-rich phase forms an at least 40% continuous layer delimited by the silicon-low regions. In an optional implementation variant, the silicon-rich phase is arranged in the silicon-low phase in the form of islands.
[0156] In the context of this application, "in island form" refers to an arrangement of discrete incoherent regions surrounded by another material, ie there are "islands" of a particular material within another substance.
[0157] In a preferred variant, the profiled sheet metal part comprises an oxide layer arranged above the anti-corrosion coating. The oxide layer is located in particular above the Al-based layer and preferably forms the outer end of the anti-corrosion coating.
[0158] The oxide layer of the formed sheet metal part consists in some degree, in particular, of more than 80% by weight of oxides, wherein the majority of the oxides (i.e., more than 50% by weight of oxides) are aluminum oxide. In addition to aluminum oxide, the oxide layer optionally contains hydroxides and / or oxides of alkali metals and alkaline earth metals, in particular magnesium oxide, either alone or as a mixture. The remainder of the oxide layer not taking into account the oxides and any hydroxides present preferably consists of silicon, aluminum, iron and / or magnesium in metallic form.
[0159] The oxide layer preferably has a thickness of at least 50 nm, in particular at least 100 nm. In addition, the thickness is preferably no more than 4 μm, in particular no more than 2 μm.
[0160] The steel matrix of the formed sheet metal has a microstructure having at least partially more than 80% martensite, preferably at least partially more than 90% martensite, in particular at least partially more than 95% martensite, more preferably at least partially more than 98% martensite. In this context, "partially having" or "partially having" means that certain areas of the formed sheet metal have the above-mentioned microstructure. In addition, certain areas of the formed sheet metal may also have different microstructures. Therefore, the formed sheet metal has the microstructure in sections or partitions.
[0161] Due to the high martensite content, very high tensile strengths and yield points can be achieved.
[0162] The present invention will be described in detail with reference to the following table.
[0163] The effect of the present invention is shown by carrying out a number of experiments. For this purpose, slabs having the composition specified in Table 1 are produced, with a thickness of 200 mm to 280 mm and a width of 1000 mm to 1200 mm, heated to the corresponding temperature T1 in a pusher furnace, and kept at T1 for 30 minutes to 450 minutes until the core of the slab reaches the temperature T1, so that the slab is penetrated and heated. The production parameters are shown in Table 2. The slabs with their respective penetration heating temperatures T1 are discharged from the pusher furnace and hot rolled. The experiments are carried out in the form of a continuous hot strip rolling operation. For this purpose, the slabs are first pre-rolled into intermediate products with a thickness of 40 mm, and the intermediate products (also called preliminary strips in hot strip rolling operations) have an intermediate product temperature T2 at the end of the preliminary rolling stage. After the preliminary rolling, the preliminary strip is immediately sent for finishing rolling so that the intermediate product temperature T2 corresponds to the initial rolling temperature of the finishing stage. The preliminary strip is rolled into a hot strip with a final thickness of 3 mm to 7 mm and with the corresponding final rolling temperature T3 specified in Table 2, cooled to the corresponding coiling temperature and coiled into a coil at the corresponding coiling temperature T4, and then cooled in still air. The hot strip is pickled and descaled in a conventional manner before cold rolling according to the cold rolling degree specified in Table 2. The cold-rolled flat steel products are heated in a tunnel annealing furnace at a dew point TP1 of -40°C to the respective annealing temperature T5 and kept at the annealing temperature for 100 seconds in each case and then cooled to the respective immersion temperature T6 at a cooling rate of 1 K / s. The cold-rolled strip with the respective immersion temperature T6 is passed through a molten coating bath at temperature T7. The composition of the coating bath is shown in Table 3. After the coating operation, the coated strip is blown in a conventional manner, resulting in a coating with different layer thicknesses (see Table 3). The strip is first cooled to 600°C at an average cooling rate of 10 K / s to 15 K / s. During the further cooling from 600°C to 450°C and from 400°C to 300°C, the strip is cooled for the cooling period t specified in Table 2. MT and t LTInternal cooling. The oxygen content and dew point TP2 here are as specified in Table 2. In the temperature range from 450°C to 400°C and below 220°C, the strip is cooled at a cooling rate of 5K / s to 15K / s in each case. Subsequently, the strip is wound into a coil using the tension specified in Table 2.
[0164] Table 4 is a summary of the combination of a certain steel variant (see Table 1) with a certain process variant (see Table 2) and a certain coating (see Table 3).
[0165] In all experiments, the thickness of the produced steel strips was between 1.4 mm and 1.7 mm.
[0166] From each steel grade thus produced, blanks were cut out for further experiments. In these experiments, the size was 200x300 mm. 2 The sheet metal sample in the form of a sheet is hot pressed from a corresponding blank. For this purpose, the blank has been heated in a heating device, for example in a conventional heating furnace, at a furnace temperature T furnace The average heating rate is r furnace (30°C to 700°C) Heating starts from room temperature. The total duration in the furnace, including heating and holding, is designated as t furnace In all cases, the dew point of the furnace atmosphere was -5°C. Subsequently, the billet was removed from the heating device and heated at a temperature T tool Inserted into the forming tool. When removed from the furnace, the blank inherits the furnace temperature. The transfer duration t consists of the duration of removal from the heating device, transport to the tool and insertion into the tool. trans In all cases, the temperature of the blank when the forming tool is inserted is T ins The blank has been formed into a corresponding formed sheet metal part in the forming tool, and the formed sheet metal part is cooled in the tool at a cooling rate r tool Cooling. The residence time in the tool is designated as t tool Finally, the samples were cooled in air to room temperature. Table 5 gives the parameters mentioned for the various variants, where "RT" is the abbreviation for room temperature.
[0167] Table 6 is a compilation of the overall results obtained for the formed sheet metal parts. The first column indicates the sample number, the steel type according to Table 1, the process variant according to Table 2, the coating according to Table 3 and the hot forming variant according to Table 5. The other columns show the composition of the alloy layer and the Al-based layer, the thickness of the oxide layer and the area-based impedance. In addition, the phase shift of the current and voltage is reported. The area-based impedance and the phase shift were each determined by the method explained at the beginning. In each case, the phase shift was less than 0.05°.
[0168]
[0169]
Claims
1. A formed sheet metal part, comprising: a) a steel matrix consisting of a steel containing 0.1 to 3 wt. % Mn and optionally up to 0.01 wt. % B, and b) an aluminum-based anti-corrosion coating provided on at least one side of the steel substrate, in, The anti-corrosion coating has an Al-based layer and an alloy layer; wherein the alloy layer is located above the steel substrate and the aluminum-based layer is located above the alloy layer; wherein the alloy layer is composed of: 35 wt% to 90 wt% Fe, 2 wt% to 12 wt% Si, optionally up to 3 wt% alkali metal or alkaline earth metal, and optional other components whose content is limited to not more than 2.0 wt% in total, and the balance is aluminum; wherein the Al-based layer is composed of: 35 wt% to 55 wt% Fe, 4 wt% to 10 wt% Si, optionally up to 3 wt% alkali metal or alkaline earth metal, and optional other components whose content is limited to not more than 2.0 wt% in total, and the balance is aluminum; and wherein the area-based impedance of the formed sheet metal is not more than 1.0 Ωcm 2 .
2. The formed sheet metal part according to claim 1, characterized in that: The formed sheet metal part includes an oxide layer disposed on the anti-corrosion coating.
3. The formed sheet metal part according to any one of claims 1 and 2, characterized in that The optional alkali metal or alkaline earth metal content of the alloy layer consists of at most 0.5 wt. % Mg, and / or the optional alkali metal and alkaline earth metal content of the Al-based layer consists of at most 0.5 wt. % Mg.
4. The formed sheet metal part according to claim 3, characterized in that: The alloy layer contains at least 0.1 wt % Mg and at most 0.3 wt % Mg, and / or the Al base layer contains at least 0.1 wt % Mg and at most 0.3 wt % Mg.
5. The formed sheet metal part according to any one of claims 1 to 4, characterized in that: The microstructure of the steel matrix of the profiled sheet metal part comprises more than 80% at least partially martensite, preferably more than 90% at least partially martensite.
6. The formed sheet metal part according to any one of claims 1 to 5, characterized in that: Steel consists, in % by weight, of iron and unavoidable impurities and of: C: 0.04 wt% to 0.45 wt%, Si: 0.02 wt% to 1.2 wt%, Mn: 0.5 wt% to 2.6 wt%, Al: 0.02 wt% to 1.0 wt%, P: ≤0.05% by weight S: ≤0.02% by weight N: ≤0.02% by weight Sn: ≤0.03% by weight As: ≤0.01% by weight Ca: ≤0.005% by weight and optionally, one or more of the elements Cr, B, Mo, Ni, Cu, Nb, Ti, V in the following contents: Cr: 0.08 wt% to 1.0 wt%, B: 0.001 wt% to 0.005 wt%, Mo: ≤ 0.5 wt%, Ni: ≤ 0.5 wt%, Cu: ≤ 0.2 wt%, Nb: 0.02 wt% to 0.08 wt%, Ti: 0.01 wt% to 0.08 wt%, V: ≤ 0.1 wt%.
7. A method for producing a formed sheet metal part according to any one of claims 1 to 6, the method comprising the following steps: a) providing a slab or thin slab consisting of a steel containing 0.1 to 3 wt. % Mn and optionally up to 0.01 wt. % B; b) penetratingly heating the slab or thin slab at a temperature (T1) of 1100° C. to 1400° C.; c) optionally, pre-rolling the through-heated slab or thin slab to obtain an intermediate product having an intermediate product temperature (T2) of 1000° C. to 1200° C.; d) hot rolling to obtain a hot rolled flat steel product, wherein the final rolling temperature (T3) is 750° C. to 1000° C.; e) optionally, coiling the hot rolled flat steel product, wherein the coiling temperature (T4) is not more than 700° C.; f) descaling the hot rolled flat steel product; g) optionally, cold rolling the flat steel product, wherein the degree of cold rolling is at least 30%; h) annealing the flat steel product at an annealing temperature (T5) of 650° C. to 900° C. in an atmosphere consisting of 2% to 15% by volume of hydrogen, the balance being nitrogen and unavoidable impurities, and having a dew point of -50° C. to 25° C.; i) cooling the flat steel product to an immersion temperature (T6) of 600° C. to 800° C., preferably 670° C. to 800° C.; j) applying an anticorrosive coating to the flat steel product which has been cooled to the immersion temperature by hot-dip coating in a melt bath having a melt temperature (T7) of 660° C. to 800° C., preferably 680° C. to 740° C., wherein the melt in the melt bath consists of 5% to 15% by weight of Si, optionally 2% to 4% by weight of Fe, optionally up to 3% by weight of alkali metals or alkaline earth metals, and optionally other components with a content limited to not more than 2.0% by weight in total and the remainder of aluminum; k) cooling the coated flat steel product to room temperature in an atmosphere containing 16% to 25% by volume of oxygen and having a dew point of -5°C to 25°C, wherein a first cooling period t in the temperature range of 600°C to 450°C MT The second cooling period t is longer than 10 seconds, in particular longer than 14 seconds, and is in the temperature range of 400° C. to 300° C. LT is more than 8 seconds, in particular more than 12 seconds; 1) optionally, subjecting the coated flat steel product to skin pass rolling; m) optionally, winding the coated flat steel product into a coil with a tension of 500 daN to 5000 daN; n) separating sheet metal blanks from coated flat steel products; o) heating the sheet metal blank so that the AC3 temperature of the blank is exceeded at least to some extent and the temperature T of the blank when inserted into the forming tool provided for the hot press forming operation is ins at least partially at a temperature above Ms+100° C., wherein Ms represents the martensite start temperature; p) Inserting the heated sheet metal blank into the forming tool, wherein the transfer time t required for removing the blank from the heating device and inserting the blank is trans No more than 20 seconds, preferably no more than 15 seconds; q) hot press forming the sheet metal blank into a formed sheet metal part, wherein during the hot press forming process the blank is subjected to a period t exceeding 1 second. tool The cooling rate r at least partially exceeds 20 K / s tool Cool to target temperature T target , and optionally maintained at that temperature; r) removing the molded product that has cooled to the target temperature T from the tool target Formed sheet metal parts.
8. The method for producing a formed sheet metal part according to claim 7, characterized in that In step j, the optional alkali metal or alkaline earth metal content consists of up to 0.5 wt.-% Mg.
9. The method for producing a formed sheet metal part according to claim 7 or 8, characterized in that: The anticorrosion coating of the cooled flat steel product obtained in step k) has an Al-based layer consisting of 5 to 15 wt.-% Si, optionally 2 to 4 wt.-% Fe, optionally up to 3 wt.-% alkali metals or alkaline earth metals and optionally further components whose content is limited to not more than 2.0 wt.-% overall and the remainder aluminum.
10. The method for producing a formed sheet metal part according to claim 9, characterized in that The content of the optional alkali metal or alkaline earth metal in the Al-based layer of the cooled flat steel product obtained in step k) consists of up to 0.5% by weight of Mg.
11. The method for producing a formed sheet metal part according to claim 9 or 10, characterized in that The anti-corrosion coating of the cooled flat steel product obtained in step k) comprises an alloy layer located above the steel substrate and an Al-based layer arranged above the alloy layer, wherein the alloy layer consists of 35% to 60% by weight of Fe and optionally other components whose content is limited to not more than 5.0% by weight in total and the remainder is aluminum.
12. The method according to any one of claims 7 to 11, wherein: The temperature reached by the sheet metal blank in step o) at least to a certain extent is Ac3 to 1000°C, preferably 850°C to 950°C.
13. The method according to any one of claims 7 to 12, wherein: The target temperature T of the formed sheet metal part target At least partly below 400°C, preferably below 300°C.
14. The method according to any one of claims 7 to 13, wherein: Steel consists, in % by weight, of iron and unavoidable impurities and of: C: 0.04 wt% to 0.45 wt%, Si: 0.02 wt% to 1.2 wt%, Mn: 0.5 wt% to 2.6 wt%, Al: 0.02 wt% to 1.0 wt%, P: ≤0.05% by weight S: ≤0.02% by weight N: ≤0.02% by weight Sn: ≤0.03% by weight As: ≤0.01% by weight Ca: ≤0.005% by weight and optionally, one or more of the elements Cr, B, Mo, Ni, Cu, Nb, Ti, V in the following contents: Cr: 0.08 wt% to 1.0 wt%, B: 0.001 wt% to 0.005 wt%, Mo: ≤ 0.5 wt%, Ni: ≤ 0.5 wt%, Cu: ≤ 0.2 wt%, Nb: 0.02 wt% to 0.08 wt%, Ti: 0.01 wt% to 0.08 wt%, V: ≤ 0.1 wt%.
Citation Information
Patent Citations
Flat steel product with an Al coating, method for producing the same, and method for producing a hot-formed steel component
EP2993248B1
Steel component produced by hot-shaping a steel flat product, steel flat product and method for producing a steel component
WO2022048990A1